Massive weight loss may facilitate otherwise impossible flap designs in phalloplasty: The first description of a tube-in-tube design of a pedicled SCIA-based flap - Wouter B. van der Sluis; Brechje L. Ronkes; Mark-Bram Bouman (JPRAS Open, 2025)
Introduction: Phalloplasty with urethral lengthening (UL) is a complex procedure with a high complication rate. Case: A 44-year-old transgender man with a surgical history of mastectomy, hysterectomy, bilateral oophorectomy, colpectomy and metadoioplasty with UL wished to undergo phalloplasty with UL. He had lost 50 kgs of weight for this procedure. There was substantial skin laxity of the whole abdominal region. A tube-in-tube pedicled SCIA-based flap was designed on the left groin area. The postoperative course was complicated by a dehiscence of the urethra, for which a retubularization was performed 10 months after surgery. At 40 months of clinical follow-up, voiding while standing was possible with good urodynamic function. Conclusion: After massive weight loss, laxity of skin may facilitate otherwise impossible phalloplasty flap designs for phalloplasty.